Application of Patent Law to Software in the IoT Context - Nabeel Mahdi Althabhawi; Jeong Chun Phuoc; Zinatul Ashiqin Zainol; Zaid Abdi Alkareem Alyasseri (Faculty of Law, Sriwijaya University, Indonesia, 2025)
The Internet of Things (IoT) is a promising field. It is estimated that around 75.44 billion devices will be connected by 2025. Undeniably, IoT will deeply impact the current intellectual property system. Many issues will be revisited and examined. This article addresses software patent protection in light of IoT. Software patent protection criteria are still embroiled in controversy. The authors examine the patentability of software in general and in the IoT context in the US, EU, UK, and Malaysian legal systems to determine the appropriate protection mechanism for software that perplexes the idea-expression dichotomy as the main premise of the copyright-patent distinction. The research is a theoretical qualitative study which traces law-related articles on IoT and software patents from multiple databases such as Hein Online and LexisNexis. The study also discussed court cases related to software and computer program patents. Furthermore, it relies on an analytical discussion of statutes and legislations in the US, EU, UK, and Malaysia, concluding that there is a conflation of computer programs and software. If the two terms are interpreted precisely in accordance with their meanings, IoT software inventions will not be at the centre of the controversy about the applicability of patent law.